Kepemimpinan Transformasional dengan Organizational Citizenship Behavior pada Karyawan: Fahmi Muhammad Fajar, Yulia Fitriani - Fahmi Muhammad Fajar; Yulia Fitriani (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2022)
The development of the industrial world in the era of globalization is increasing rapidly.Successful companies need people who do moretheir usual job, which exceeds expectations. In a dynamic world of work today, where more and more tasks are carried out by teams and flexibility is very important, civilly engaged employees help others on the team them, volunteering for additional work, avoiding conflict unnecessary, they obey the spirit and the rules and regulations, and with friendly tolerating coercion and occasional work-related distractions is organizational citizenship behavior (OCB). Many things leadership style can be done by a leader, one of which is leadership transformational behavior that will encourage the growth of mutually helpful behavior and help voluntarily. One of the factors that can influence organizational citizenship behavior, namely transformational leadership. This study aims to determine whether there is a relationship between transformational leadership with organizational citizenship behavior in employees of PT. Patra Trading Plumpang 3. The subjects of this research are all production employees of PT. Patra Trading Plumpang 3 155 subjects. Data analysis using the Pearson correlation technique and obtained a sig value of 0.000 (P < 0.005) it can be concluded that there is a significant positive relationship between transformational leadership with Organizational Citizenship Behavior to employees of PT. Patra Trading Plumpang 3, and the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.